End-to-end network collaboration in 5G networks - Yiliang LIU; Xin LI; Kaitao BO (Dianxin kexue)
The advent of 5G network era puts forward higher requirements for telecom operators’ networks.The current situation,overall coordination framework and key capabilities of wireless access network,bearer network and core network in network slice were mainly described from the perspective of 5G end-to-end network coordination key technology,the actual case scenario of end-to-end slice was introduced,helping operators to successfully transform the network,one network multi-purpose was completed,network construction cost was reduced and differentiated service capacity was improved.